Pengaruh Bauran Pemasaran Jasa Terhadap Keputusan Menginap di Hotel Andita Syariah Surabaya - Desy Kavanillah; Ahmad Ajib Ridlwan (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2018)
This research is aimed at examining the influence of service marketing mix towards visitor’s decision to stay in Andita Syariah Hotel Surabaya. The independent variable on this research are product, price, place, promotion, people, process, pyhsical evidence, promise, patience. While the dependent variable is decision to stay which consist of four indicators, they are product choice, brand choice, distribution choice and time to stay. Data analysis technique on this research used classic assumption test, multiple linear regression analysis, F-test and T-test. The result of this research shows that the service marketing mix has a simultaneous influence towards the decision to stay in Andita Syariah Hotel Surabaya. While based on partial test, there are three variables of the service marketing mix which significantly influence variable decision to stay, they are place, physical evidence and promise.